2015
DOI: 10.3141/2534-14
|View full text |Cite
|
Sign up to set email alerts
|

Placement of Rapid Transit Park-and-Ride Facilities

Abstract: This study assessed the state of the practice in figuring out the placement of new rapid transit park-and-ride facilities and whether the existing body of literature was still in harmony with today's practice. The analysis was based on free-form interviews and a survey of transit professionals. The results revealed several emerging differences that had not been discussed in the literature. First, the cost of the park-and-ride facility was of critical importance to transit planners, as the pressure to deliver p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The former provided comprehensive guidelines on PNR lot design and dimensions, and the latter offered distinct guidelines for PNRs of high density, medium density, and low density areas. However, these existing Guidelines and Best Practice reports did not document some important but contradictory PNR location decisions, which were identified by Mock and Thill (2015). These researchers reported that PNR location preferences might differ between planners and transit agency managers.…”
Section: Theme 2: Guidelines and Best Practicesmentioning
confidence: 99%
“…The former provided comprehensive guidelines on PNR lot design and dimensions, and the latter offered distinct guidelines for PNRs of high density, medium density, and low density areas. However, these existing Guidelines and Best Practice reports did not document some important but contradictory PNR location decisions, which were identified by Mock and Thill (2015). These researchers reported that PNR location preferences might differ between planners and transit agency managers.…”
Section: Theme 2: Guidelines and Best Practicesmentioning
confidence: 99%
“…As is widely considered, P & R systems have played an essential role in the encouragement of the shift of passengers from private vehicles to public transportation [12,13,[15][16][17][18][19][20][21]. Therefore, the facility's location is close to the public transport system stops.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The P&R system is a set of facilities distributed throughout the urban environment of a city to establish a connection point or modal interchange to transfer private vehicle users to a more sustainable mode of transport, such as public transport [1]. In other words, the Park and Ride system is closely linked to parameters of private and public transport [2]. Private vehicle users who live in areas outside the urban perimeter (origin of the trip) or where there is few or no direct connection to public transport wish to commute daily to their destination.…”
Section: Introductionmentioning
confidence: 99%